Relationship Between Psychological Flexibility and Professional Quality of Life in Nurses Working in Psychiatric Clinic - Lale Ünver Aydın; Erman Yıldız (Artuklu Health)

(untitled)
Introduction: This study aims to evaluate the association between psychological flexibility and the professional quality of life of nurses working in a mental clinic.Methods: In an eastern Turkish mental health facility, 151 nurses participated in this descriptive and correlational study. Surveys prepared through Google Forms were shared with nurses using WhatsApp groups. The study used the “Personal Information Form”, “Psychological Flexibility Scale” and “Professional Quality of Life Scale”, to evaluate the psychological flexibility and quality of life of psychiatric nurses. The data was collected online and analyzed in the SPSS 26.0 program.Results: Based on the results of the analysis, nurses' psychological flexibility levels were found to be above average, professional satisfaction levels were found to be below average, and burnout and empathy fatigue levels were found to be moderate. Psychological flexibility, occupational satisfaction, and empathy fatigue were found to be significantly positively correlated; however, burnout was not found to be significantly correlated. Psychological flexibility explained 20.3% of professional satisfaction and 7.8% of professional quality of life.Conclusion: This study showed that the psychological flexibility of psychiatric nurses positively affected their professional quality of life. Implementation of psychosocial approaches based on acceptance and mindfulness strategies to increase the psychological flexibility of nurses and to improve professional satisfaction.